The Influence of Flexible Work Arrangements and Work-Life Balance on Generation Z Career Development Mediated by Job Satisfaction - Fatimah Wahyu Ermawati; Muhammad Halim Maimun (Jurnal Economic Resource, 2026)
This study, entitled “The Influence of Flexible Work Arrangements and Work–Life Balance on Generation Z Career Development Mediated by Job Satisfaction,” aims to examine the relationships between flexible work arrangement (FWA), work–life balance (WLB), job satisfaction, and career development among Generation Z in the Solo Raya region. Generation Z residents of Solo Raya constitute the study’s population, and a sample of 100 respondents was selected using purposive, non-probability sampling. A closed-ended online survey was used to gather data, and SEM-PLS with SmartPLS 4.0 was used for analysis. The results indicate that, while flexible work arrangements do not directly and significantly affect career development, work-life balance has a positive and significant impact on it. However, work-life balance and flexible work arrangements both significantly and positively impact job satisfaction, which, in turn, has a significant and favorable effect on career development. Furthermore, it has been shown that job satisfaction partially mediates the effects of flexible work arrangements and work-life balance on Generation Z's growth.